Forecasting the Resilience and Stability of Indonesian Islamic Banking in the Face of Global Economic Uncertainty in 2030 - Gadis Arniyati Athar; T. Citra Nisa Farza; Muhammad Fitri Rahmadana; Nayla Salsabila Batubara (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study aims to explore the stability and resilience of Islamic banking in the face of the 2030 global recession, providing a foundation for managerial implications in the world of Islamic banking. This research uses a quantitative approach with resilience indicators such as Return on Assets (ROA) and Non-Performing Financing (NPF), and stability indicators such as Capital Adequacy Ratio (CAR) and Financing to Deposit Ratio (FDR). The data used is secondary data from the financial statements for the period from the Q1 of 2019 to the Q4 of 2024. To provide an overview and to forecast of the level of resilience and stability, the ARIMA method is used. To illustrate the interrelationship and interaction, as well as the magnitude of the contribution of resilience variables to stability variables (CAR and NPF) with stability (ROA and FDR) in Islamic Banking in Indonesia, the VECM method is used. The analysis results show that overall, the CAR is in the very healthy category, although some banks experienced a decline at the end of 2024. NPF experienced a surge during the recession but tended to stabilize afterward. Meanwhile, ROA and FDR fluctuated due to global economic pressures but showed a stable long-term trend. VECM model estimates indicate a significant relationship between variables, where FDR and NPF influence ROA in the long run, while CAR plays more of a risk buffer role. This finding emphasizes the importance of capital optimization, strengthening risk management, and balance in intermediation functions to maintain the sustainability of the Islamic banking sector amidst global economic uncertainty toward 2030.Penelitian ini bertujuan untuk mengeksplorasi stabilitas dan ketahanan perbankan syariah dalam menghadapi resesi global 2030, untuk kemudian memberikan landasan bagi implikasi manajerial dalam dunia perbankan syariah. Penelitian ini menggunakan pendekatan kuantitatif dengan indikator ketahanan keuangan seperti Return on Assets (ROA) dan Non-Performing Financing (NPF), dan indikator stabilitas seperti Capital Adequacy Ratio (CAR) dan Financing to Deposit Ratio (FDR). Data yang digunakan adalah data sekunder dari laporan keuangan untuk periode dari Q1 tahun 2019 hingga Q4 tahun 2024. Untuk memberikan gambaran dan peramalan tingkat ketahanan dan stabilitas, digunakan metode ARIMA. Untuk menggambarkan interelasi dan interaksi, serta besarnya kontribusi variabel ketahanan terhadap variabel stabilitas (CAR dan NPF) dengan stabilitas (ROA dan FDR) pada Perbankan Syariah di Indonesia, digunakan metode VECM. Hasil analisis menunjukkan bahwa secara keseluruhan, CAR berada dalam kategori sangat sehat, meskipun beberapa bank mengalami penurunan di akhir tahun 2024. NPF mengalami lonjakan selama resesi tetapi cenderung stabil setelahnya. Sementara itu, ROA dan FDR berfluktuasi akibat tekanan ekonomi global tetapi menunjukkan tren jangka panjang yang stabil. Estimasi model VECM menunjukkan hubungan yang signifikan antar variabel, di mana FDR dan NPF memengaruhi ROA dalam jangka panjang, sementara CAR lebih berperan sebagai penyangga risiko. Temuan ini menekankan pentingnya optimalisasi permodalan, penguatan manajemen risiko, dan keseimbangan fungsi intermediasi untuk menjaga keberlanjutan sektor perbankan syariah di tengah ketidakpastian ekonomi global menuju tahun 2030.